2016
DOI: 10.1186/s12877-016-0259-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of health related quality of life following low-trauma fractures in the elderly

Abstract: BackgroundTo estimate the long-term change in health related quality of life (HRQoL) following low-trauma fractures among individuals receiving home care (HC) services or living in long-term care (LTC) facilities using linked healthcare administrative data from Ontario, Canada.MethodsHRQoL was estimated using the Health Utility Index (HUI-2) with the InterRai Minimum Data Set (MDS), a mandatory questionnaire for LTC and HC in the province of Ontario (population 14 million). The HUI-2, a validated HRQoL instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 25 publications
2
33
0
5
Order By: Relevance
“…Thus, we can say that women with hip fractures failed to recover to baseline. Tarride and colleagues reported that none of the participants living in home care or long‐term care centers recovered to their baseline after 3 years postfracture for all fracture types. Notwithstanding that vertebral fractures are associated with increased mortality, we found that of the women who survived such fractures, they improved to their prefracture level after 5 years or more.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we can say that women with hip fractures failed to recover to baseline. Tarride and colleagues reported that none of the participants living in home care or long‐term care centers recovered to their baseline after 3 years postfracture for all fracture types. Notwithstanding that vertebral fractures are associated with increased mortality, we found that of the women who survived such fractures, they improved to their prefracture level after 5 years or more.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture prevention strategies are important to avoid the burden of mortality and decreased quality of life for NH residents . The observed resident differences suggest nonhip LE fractures may have a different mechanism of injury than hip fractures and may occur without a fall.…”
Section: Resultsmentioning
confidence: 99%
“…A standardised depression screening tool, the 9‐item Patient Health Questionnaire (PHQ‐9; Kroenke, Spitzer, & Williams, ), was introduced as a component of the minimum data set , version 3.0 ( mds 3.0) in October 2010 (Saliba & Buchanan, ). The MDS (Morris et al., ) is a set of internationally used (Chen et al., ; Tarride et al., ) instruments to conduct a comprehensive assessment of nursing home residents, and its use is federally mandated in the USA for all certified institutions receiving Medicaid and Medicare funding. Medicaid is a joint federal and state programme to assist persons with limited resources with medical costs; Medicare is a federal health insurance programme for people aged 65 and older, and for those with disabilities or end‐stage renal disease.…”
Section: Introductionmentioning
confidence: 99%